A Source Based Analysis of Lexical Collocation Errors among Iraqi Teachers of English - Inst.Atyaf Hasan Ibrahim; Eman Riyadh Adeeb (International Journal of Psychosocial Rehabilitation, 2020)
In everyday life usage of language, people use collocations in their written as well as spoken language. Collocations are very important to produce correct and understandable language, thus collocations became the main concern of many researches. Therefore, this study attempts to investigate lexical collocational errors, made by Iraqi EFL teachers . The sample of the study includes (20) teachers of English secondary schools in Diyala governorate/Baqubah district, distributed on two groups (10) each. The data was collected systematically via recording the teachers’ lectures on different topics for over 60 lectures, each of one hour long, then analyzing the data to shed light on the problems they were constantly confronted with. Lexical collocation errors were analyzed quantitatively and qualitatively to trace the fundamental barriers related to such inevitable errors, and thus suggested some ways to brace those teachers’ collocational knowledge. The study reached the conclusions that those mistakes are committed due to the negative effect of the mother tongue and the lack of sufficient information about the correct collocations that should be used in English language, in addition to the teachers’ concentration on the scientific material rather than the language used.